Characterization of a temporoparietal junction subtype of Alzheimer's disease. Issue 14 (26th June 2019) - Meyer, François; Wehenkel, Marie; Phillips, Christophe; Geurts, Pierre; Hustinx, Roland; Bernard, Claire; Bastin, Christine; Salmon, Eric
Abstract: Alzheimer's disease (AD) subtypes have been described according to genetics, neuropsychology, neuropathology, and neuroimaging. Thirty‐one patients with clinically probable AD were selected based on perisylvian metabolic decrease on FDG‐PET. They were compared to 25 patients with a typical pattern of decreased posterior metabolism. Tree‐based machine learning was used on those 56 images to create a classifier that was subsequently applied to 207 Alzheimer's Disease Neuroimaging Initiative (ADNI) patients with AD. Machine learning was also used to discriminate between the two ADNI groups based on neuropsychological scores. Compared to AD patients with a typical precuneus metabolic decrease, the new subtype showed stronger hypometabolism in the temporoparietal junction. The classifier was able to distinguish the two groups in the ADNI population. Both groups could only be distinguished cognitively by Trail Making Test‐A scores. This study further confirms that there is more than a typical metabolic pattern in probable AD with amnestic presentation.